The dynamic characteristics and influencing factors of debt structure of the public companies in China - Zhefan Piao; Xiaoqi Feng (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: In a macroeconomic environment with the non-tradable shares reform, financial crisis, tax reform and monetary policy, to examine the dynamic characteristics and factors of the debt maturity structure, this research tends to offer an empirical analysis about Chinese listed companies in different industries. Design/methodology/approach: Learned from Leary (2009), Voutsinas and Werner (2011), this study designs a model of debt maturity structure with an unbalanced panel data set. Consists of 1352 Chinese listed companies with 8124 observations during the period of 2003-2011, the sample passed Hausman test, and the findings support the fixed effects model. Findings: Besides the factors that have been confirmed by previous researches, debt maturity structure is also sensitive to other factors, such as economic expectations, monetary policy, financial restrictions and changes in tax rates. Research limitations/implications: There are still many cases, which affect the debt maturity structure, are worth of further exploring, for instance, the impact of lagged monetary policy, the determinants of short-term debt ratio and the cost of operating. Practical implications: From the macro point of view, research in this area enables the government to introduce more suitable policies that direct and promote the development of the bond market. From the micro point of view, it spurs corporations to choose proper finance structure. Firms can learn from the research to adopt the efficient method and term of financing as well as debt structure. Originality/value: In some way, conclusions of this paper contribute to the study of dynamic characteristics and factors of debt maturity structure in Chinese listed companies.
Keywords: 650; maturity structure; debt structure; dynamic characteristics; panel data